End‐of‐life care in a rehabilitation centre for older people in Australia. (31st January 2013) - Tan, Heather; Digby, Robin; Bloomer, Melissa; Wang, Yixin; O'Connor, Margaret
<x xml:space="preserve">Abstract</x> Aim To investigate processes at the end of life for patients who died in a subacute evaluation and management facility for older people. Methods A retrospective chart audit for patients (n = 55) who died in the previous 2 years was undertaken, recording a number of significant variables. Results Despite diagnosis of comorbid medical conditions, most participants were admitted for improved functioning or assessment for alternative accommodation. Consistent with this focus, the key contact person was most often an allied health team member. Not For Resuscitation order and/or power of attorney documents on admission were uncommon (<30%) as were referrals to palliative care specialist staff (13%), although an end‐of‐life discussion was recorded (90%) and often included as a new goal of care (71%). Conclusion Factors likely to improve end‐of‐life care include advance care planning, earlier recognition of short prognosis and staff education.